RADHA SHYAM NARRATOR'S VISION OF THEATRE AND PARSI THEATRE ART - Mani, Alka (ShodhKosh: Journal of Visual and Performing Arts, 2024)
When the Indian acting tradition and acting style are combined, the Parsi acting method emerges in its unique form. It is during this period of change that many famous actors and actresses emerge. India has had a rich tradition of folk theatre for a long time, but its slavery suppressed this tradition to a great extent and limited the scope of folk theatre. The natural craftsmanship that this folk theatre gave to India, combined with the craftsmanship of the English theatre, was born again in a new form in the middle of the nineteenth century. The presentation process and plot of the Parsi theatre are determined by the political, economic, social and cultural conditions of its era. The actors, playwrights of the Parsi theatre were dependent on those directors and the owners of the company; Radheshyam Kathavachak had a clear vision about acting and character. Acting is unique in itself, all that deficiency can be fulfilled by acting but selection of characters according to character is necessary.